Species distribution and resistance profile of medical importance bacteria isolated from lesions of cats with sporotrichosis (Research, Society and Development, 2021)
Sporotrichosis is an infection with zoonotic potential caused by the Sporothrix schenckii complex. It is widely distributed worldwide. The cutaneous form is the most common presentation of the disease. The cat is one of the main animals affected, having numerous fungal cells in its lesions, becoming an important fungi disseminator. Due to the type of skin lesion caused by the fungus, secondary bacterial infections commonly occur. The aim of the present study was to learn about the most common bacterial agents involved in feline lesions with sporotrichosis, as well as their resistance profile to antimicrobial agents. The faster the treatment of bacterial and fungal infections is controlled, the faster the lesions heal. Consequently, the transmission of the disease is controlled. Samples of skin lesions or nasal discharge from 18 domiciled or semi-domiciled cats diagnosed with sporotrichosis were collected. Cats were evaluated for secondary bacterial infections. The samples were processed to isolate aerobic bacteria that were later identified by MALDI TOF. Susceptibility was assessed using the disk diffusion method for a total of 17 antimicrobial agents. The main species identified were Staphylococcus aureus and Staphylococcus felis. Proteus mirabilis has also been identified in some samples. Among these microorganisms, two strains of S. aureus were identified as resistant to methicillin. The TSA's results showed sensitivity to most of the tested antimicrobials. Staphylococcus was the most identified genus in skin lesions and nasal secretions of cats with sporotrichosis. Most microorganisms were sensitive to fluoroquinolones and aminoglycosides. Penicillins and cephalosporins showed less potential for action on these bacteria, which showed greater resistance to these classes.